Wide-Bandgap Perovskite/Gallium Arsenide Tandem Solar Cells - Li, Zijia; Kim, Tae Hak; Han, Sung Yong; Yun, Yeo Jun; Jeong, Seonghwa; Jo, Bonghyun; Ok, Song Ah; Yim, Woongbin; Lee, Seung Hu; Kim, Kangho; Moon, Sunghyun; Park, Ji Yong; et al. (Advanced Energy Materials, 2020)
Gallium arsenide (GaAs) photovoltaic (PV) cells have been widely investigated due to their merits such as thin-film feasibility, flexibility, and high efficiency. To further increase their performance, a wider bandgap PV structure such as indium gallium phosphide (InGaP) has been integrated in two-terminal (2T) tandem configuration. However, it increases the overall fabrication cost, complicated tunnel-junction diode connecting subcells are inevitable, and materials are limited by lattice matching. Here, high-efficiency and stable wide-bandgap perovskite PVs having comparable bandgap to InGaP (1.8–1.9 eV) are developed, which can be stable low-cost add-on layers to further enhance the performance of GaAs PVs as tandem configurations by showing an efficiency improvement from 21.68% to 24.27% (2T configuration) and 25.19% (4T configuration). This approach is also feasible for thin-film GaAs PV, essential to reduce its fabrication cost for commercialization, with performance increasing from 21.85% to 24.32% and superior flexibility (1000 times bending) in a tandem configuration. Additionally, potential routes to over 30% stable perovskite/GaAs tandems, comparable to InGaP/GaAs with lower cost, are considered. This work can be an initial step to reach the objective of improving the usability of GaAs PV technology with enhanced performance for applications for which lightness and flexibility are crucial, without a significant additional cost increase.
Keywords: Efficiency improvement; Indium gallium phosphide; Phase segregations; Tandem cells; Tandem configuration; Tandem solar cells; Tunnel junction diode; Wide band gap; gallium arsenide; perovskite/GaAs tandem cells; phase segregation; thin-film flexible tandem cells; wide-bandgap perovskites